2020
DOI: 10.1590/0037-8682-0399-2020
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic analysis of biofilm production by Pseudomonas aeruginosa isolates from infection and colonization samples

Abstract: Introduction: Pseudomonas aeruginosa is an opportunistic pathogen associated with healthcare-related infections, affecting mainly patients with underlying diseases and immunosuppression. This microorganism has several virulence mechanisms that favour its pathogenesis, including the production of biofilm. This study aimed to analyze the phenotypic production of biofilms, the occurrence of quorum sensing (QS) genes, and the clonal profile of clinical isolates of P. aeruginosa from colonized/infected patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…13 In contrast, Rodrigues et al reported that maximum isolation rate of P. aeruginosa from blood (33.3%), tracheal secretion (23.8%), and urine (23.8%) was the most prevalent sources of P. aeruginosa. 16 There was a high prevalence of biofilm production in these isolates. Furthermore, Haji reported that, out of 96, 84 (87.5) isolates were biofilm producers by MTPM method.…”
Section: Discussionmentioning
confidence: 91%
“…13 In contrast, Rodrigues et al reported that maximum isolation rate of P. aeruginosa from blood (33.3%), tracheal secretion (23.8%), and urine (23.8%) was the most prevalent sources of P. aeruginosa. 16 There was a high prevalence of biofilm production in these isolates. Furthermore, Haji reported that, out of 96, 84 (87.5) isolates were biofilm producers by MTPM method.…”
Section: Discussionmentioning
confidence: 91%
“…11 Biofilm formation helps the organism survive on medical devices and enhances drug resistance in P. aeruginosa , thereby contributing to chronic infections in patients on mechanical ventilators, with burn wounds and cystic fibrosis. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…of proteins that maintain adhesion, and thus the deletion of individual proteins in "C. albicans" , such as "bcr1", resulted in an almost complete loss of initial adhesion. and a collapse of biofilm, development(Burgain et al, 2019;Rodrigues et al, 2020;van Wijlick et al, 2016). highlighted that biofilm maturation.…”
mentioning
confidence: 99%